The Just War Theory: Accounting Jus Post Bellum - Mohd Rizal Yaakop; Sharifah Aluya Ali; Sharifah Sabrina Ali; Iing Nurdin; Farhatul Mustamirah; Ahmad Ali Seman; Ahmad Redzuan Mohamad; Mohd 'Azmi Mohd Razif (Human Resource Management Academic Research Society, 2025)
A Just War Theory is a moral doctrine about the use of force. It underlines certain basic principles of waging war, starting from the intention to wage war until the conduct of soldiers during war, known to be jus ad bellum ( the resort to war), jus in bello ( the actual conduct of war), and the most recent development jus post bellum ( justice after war). As propagated, Just War Theory legitimized the use of force as long as all the requirements of its principles has been fulfilled; first is the principle of jus ad bellum lays the justifying requirements for why war is waged, namely just cause, legitimate authority, right intention, proportionality, probability of success and war as the last resort. Second is the principle of jus in bello, the justifying principle governing the conduct within war, namely proportionality, right intention as well as the issue of noncombatant immunity